Pengembangan Aplikasi Android Rekomendasi Tempat Pembelian Kuliner Korea dengan GDSS dan LBS (Studi Kasus: Kota Malang) - Wanda Septia Dewi Lestari; Ratih Kartika Dewi; Komang Candra Brata (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
As the time goes by, culinary business has become one of many factors that influences the culinary in many Indonesia regions to adapt with the culinary from Korea. Malang is one of them. There are many Indonesians who are interested in this ginseng country culinary. The survey shows that it is hard for the respondents to decide where they want to go to eat that is suitable with their preferences. Other than that, many customers have different preferences from their friends or other group members to decide which Korean restaurant they are going to choose. There for, the aim of this research is to develop an app to recommend places to buy Korean food in Malang with Group Decision Support System (GDSS) and Location Bases Services (LBS) based in Android. TOPSIS-BORDA algorithm is used to get the group recommendation. There are 5 criteria used which are lowest price, rating, operational hour, facility and the distance from user's location to the restaurant. The result of Black Box testing on the functional requirements is 100% valid. The result of algorithm validation is 100% valid. It was done by comparing the result from the system and the manual calculation. And the result of the usability testing is 75 which categorized as good, grade scale C and acceptable. It means that the application is accepted by the users.